Facial Profile Of Bataknese Based On Nose, Lips And Chin Proportions - Bahirrah, Siti (IIUM Medical Journal Malaysia, 2017)
Introduction: The success of orthodontic treatment is often associated with the improvement of facial appearance. Soft tissues of the nose, lips and chin are important factors in determining the beauty of the face. The aim of this study was to determine the facial profile of the Bataknese based on the proportion of soft tissue facial components such as nose, lips and chin. Materials and Methods: This research was an observational study with a cross-sectional design. The samples of this research consists of 48 Batak tribe students in FKG USU Medan. This research was carried out by using 48 lateral cephalometry obtained from Batak tribe students who fit the inclusion criteria.Determination of soft tissue facial profile was carried out with Skinazi method. Results: The mean proportion results obtained from the soft tissue facial components of the nose was 64.41%, upper lip 13.79%, lower lip 14.80% and chin 6.86%. The results showed soft tissue facial profile obtained descriptively from the Bataknese were highest in nose proportion followed by lower lip, upper lip and the smallest were chin proportion. Large proportion of the nose and small proportion of chin showed that facial profile of the Bataknese were convex. The results of t- test and Mann Whitney analysis of nose, upper lip, lower lip and chin proportion showed there were no difference between male and female (p>0.05). Conclusion(s): The findings of this research showed that the soft tissue facial profile based on nose, lips and chin propotions in male and female from Batak tribe were convex.